1990
DOI: 10.1080/07315724.1990.10720410
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipoprotein profiles during intense military training.

Abstract: The effects of intense military training on lipoprotein concentrations were monitored in a group of 44 Navy trainees. Dietary intakes and lipoprotein profiles were obtained before and after 5 weeks of physical conditioning and after 5 days of continuous, extremely intense physical and psychological stress. Body weight did not change significantly and dietary intakes were consistently high in saturated fat and cholesterol. After physical conditioning, serum total cholesterol and triglyceride concentrations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Following 5 days of “Hellweek,” a further decrease in TC (–17.2%) and LDL-C (–30%) with an increase in HDL-C (+12.1%) was observed. Throughout, TG was unchanged at the observed sampling time points 37 . Additionally, 12-weeks of military training in Israeli recruits resulted in an increase in body weight 36 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Following 5 days of “Hellweek,” a further decrease in TC (–17.2%) and LDL-C (–30%) with an increase in HDL-C (+12.1%) was observed. Throughout, TG was unchanged at the observed sampling time points 37 . Additionally, 12-weeks of military training in Israeli recruits resulted in an increase in body weight 36 .…”
Section: Discussionmentioning
confidence: 90%
“…The changes in lipid panel parameters found in this study are similar to others involving training periods of military recruits. 36,37 Smoak et al 37 previously investigated the diets and serum lipoprotein concentrations of US Navy SEAL candidates during the first 7weeks of their training program. The program involves a 5-week conditioning program followed by ''Hellweek,'' marked by 113 hours of physical and psychological stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, other researchers found results different to ours. In fact, using intense physical conditioning, Smoak, et al observed no change in lipid profile among participant to his study [15]. This difference may be after 6 days of inactivity in overweight subjects [20].…”
Section: Insulin Sensitivity Measurement: Insulin Sensitivity Was Refmentioning
confidence: 72%
“…Investigation of metabolic biomarkers (cholesterol levels, albumin, and glycosylated hemoglobin) and immune system biomarkers (interleukin-6, tumor necrosis factor-alpha, and C-reactive protein) helps to confirm the induction of stress conditions (Kriegler et al, 1988;Smoak et al, 1990;Pace et al, 2009). These markers reflect the stress-related metabolic and immunological changes in COVID-19 patients.…”
Section: Covid-19 Induced Stressmentioning
confidence: 99%